Prevalence of Diabetic Retinopathy in Patients with DM-2 Patients - Mohammad Munib, Ubaidullah, Zarak Khan, Yasir Khurshid, Seema Mohmand, Shahab Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: One of the main microvascular complications of type 2 diabetes mellitus and a significant contributor to avoidable blindness globally is diabetic retinopathy. To lessen vision loss, early identification and treatment are essential. The purpose of this research was to ascertain the prevalence of DR and related risk variables in a tertiary care hospital’s DM-2 patients. Methodology: Over the course of a year, this cross-sectional research was carried out at the Department of Community Medicine, Swat Teaching Hospital. Consecutive sampling was used to cover 115 individuals with type 2 diabetes mellitus (DM-2). Fundoscopic examination was used to detect diabetic retinopathy (DR), which was then divided into three categories: diabetic macular edema (DME), proliferative diabetic retinopathy (PDR), and non-proliferative diabetic retinopathy (NPDR). We gathered information on blood pressure, BMI, HbA1c levels, demographics, and the length of diabetes. Chi-square tests, t-tests, and logistic regression were used for statistical analysis; a p-value of less than 0.05 was deemed significant. Results: The total prevalence of DR was 37.4% (n=43), with NPDR accounting for 27.0% (n=31) and PDR for 10.4% (n=12). 13.9% (n=16) of the patients had DME. Compared to patients without DR, those with DR had higher HbA1c levels (mean: 8.4 ± 1.2%, p = 0.018) and a substantially longer duration of diabetes (mean: 11.2 ± 4.5 years, p = 0.045). According to logistic regression, poor glycemic management (OR = 2.65, p = 0.018) and a longer duration of diabetes (OR = 2.21, p = 0.032) were independent predictors of DR. There was no significant correlation between DR and BMI or hypertension (p > 0.05). Conclusion: DR was highly prevalent (37.4%), with poor glycemic control and longer diabetes duration being key risk factors. Early screening and strict diabetes management are essential for prevention. Keywords: Diabetic retinopathy, type 2 diabetes mellitus, prevalence, risk factors, glycemic control, diabetes duration, Pakistan.